MENJELAJAH DAMPAK GLOBALISASI BERBASIS METODE FIELD TRIP BAGI SISWA SD - Lisa Andriani; Hamdan Tri Atmaja; Erni Suharini; Harianingsih; Eka Titi Andaryani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research examines the effectiveness of the field trip method in helping 6th grade elementary school students understand the impact of globalization. The research approach is qualitative-descriptive. This research involved 25 students from SD Negeri Kaligangsa 3 Tegal City on field trips to various locations in Tegal city which showed the influence of globalization. Data was collected through participant observation, semi-structured interviews, and analysis of student reflections. The field trip method has proven to be effective in bridging theory and practice, increasing student involvement, and developing critical observation skills. This research provides valuable insight into innovative strategies in social studies learning at the elementary school level and the importance of direct experience in understanding global-local phenomena. The concept of experiential learning that underlies the field trip method is discussed comprehensively by Dewi (2020), who emphasizes the importance of direct experience in students' knowledge construction. Prasetyo (2021) researched the effectiveness of field trips in increasing students' understanding of contemporary social issues, including globalization. In the context of globalization learning at the elementary school level, Suharto (2022) explains the importance of simplifying complex concepts into concrete examples that students can observe in everyday life. This research strengthens the opinion of using the field trip method in learning globalization.